Enantioselective Synthesis of Axially Chiral Silacyclohexylidene Oxime Ethers by Chiral Phosphoric Acid Catalysis - Wang, Xi-Yu; Xie, Xiao-Zhou; Wu, Zhong-Wei; Bai, Yang; Chen, Guangying; Yu, Jin-Sheng (Synthesis, 2024)
The first asymmetric condensation of prochiral silacyclohexanones with hydroxylamines by chiral phosphoric acid catalysis has been developed, which provides a facile and straightforward protocol for the enantioselective construction of valuable axially chiral silacyclohexylidene oxime ethers that are otherwise inaccessible. Notably, this constitutes a rare example for accessing silacycles featuring axial chirality.
Keywords: axial chirality; chiral phosphoric acids; silacyclohexanones; enantioselective condensation